2005
DOI: 10.1109/tbme.2004.840471
|View full text |Cite
|
Sign up to set email alerts
|

Minimum-Time Thermal Dose Control of Thermal Therapies

Abstract: The problem of controlling noninvasive thermal therapies is formulated as the problem of directly controlling thermal dose of the target. To limit the damage to the surrounding normal tissue, the constraints on the peak allowable temperatures in the selected spacial locations are imposed. The developed controller has a cascade structure with a linear, constrained, model predictive temperature controller in the secondary loop. The temperature controller manipulates the intensity of the ultrasound transducer wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 31 publications
5
32
0
Order By: Relevance
“…It has been found that peak temperature in the range of 60-80°C is required to ensure complete tumor necrosis without any post-treatment trauma [19]. However, it has been also observed that temperature required to kill the tumor tissue depends on the exposure time [20,21]. Robinson et al [22] has predicted that temperature elevation to at least 56°C for 1 s or more should be sufficient to kill cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that peak temperature in the range of 60-80°C is required to ensure complete tumor necrosis without any post-treatment trauma [19]. However, it has been also observed that temperature required to kill the tumor tissue depends on the exposure time [20,21]. Robinson et al [22] has predicted that temperature elevation to at least 56°C for 1 s or more should be sufficient to kill cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The low-dimensionality of the identified models and image compression is important for the real-time implementation of model-based treatment control system with MRI feedback, especially in the case of computationally expensive controllers, such as optimizing, predictive controllers described in [18], [15], [19], [20].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…With the available patient- and site-specific heat deposition and dissipation models (collectively, treatment model), the optimization of the treatment plan becomes possible and may include the selection of appropriate applicators, their spatial positioning, and the configuration of the temperature monitoring system. Model-based automatic treatment control systems can provide such advanced functionality as minimization of the treatment time without exceeding the maximum allowable temperature in the normal tissues [5], [6]. …”
Section: Introductionmentioning
confidence: 99%